The temperamental basis of extraversion and its implications for psychopathology. (February 2022) - Watson, David; Clark, Lee Anna; Khoo, Shereen
Abstract: Many individuals—including Eysenck, Gray, Strelau, and Depue—have helped to explicate the temperamental basis of extraversion. The current study builds on this work by examining how two positively correlated aspects of extraversion—agentic extraversion (i.e., individual differences in reward anticipation and incentive motivation) and communal extraversion (i.e., individual differences in consummatory pleasure)—relate to psychopathology. We examined these relations in two samples. We extended previous work by analyzing three pairs of communal and agentic extraversion scales. These scales generally showed strong convergent and discriminant validity across samples. We assessed psychopathology using selected scales from the Comprehensive Assessment of Traits relevant to Personality Disorder (CAT-PD; Wright & Simms, 2014). Structural analyses of these CAT-PD scales revealed that the same two factors emerged in both samples; they were labeled Detachment (e.g., Anhedonia, Social Withdrawal) and Externalizing (e.g., Grandiosity, Risk Taking). All three indicators of communal extraversion were strongly negatively related to Detachment, whereas all three measures of agentic extraversion were moderately positively associated with Externalizing, thus demonstrating high replicability across measures and samples. Finally, regression results established that the unique component of communal extraversion is healthy and adaptive, whereas the unique component of agentic extraversion is largely maladaptive in nature. Highlights: Detachment is a dimension characterized by anhedonia and social aloofness. Externalizing is a dimension characterized by grandiosity, rudeness and risk taking. Detachment is strongly negatively related to the communal aspect of extraversion. Externalizing is positively related to the agentic aspect of extraversion. These results replicate across 2 samples and 3 different measures of extraversion.